Chemoradiotherapy in the treatment of locally advanced cervical cancer - Daukantienė, Lina; Valuckas, Konstantinas Povilas; Aleknavičius, Eduardas; Pipirienė-Želvienė, Teresė (Lietuvos chirurgija, 2013)
The purpose of this article is overview of currently available knowledge found in literature about the chemoradiation for locally advanced cervical cancer. Cervical cancer is the third most commonly diagnosed cancer and the fourth leading cause of cancer death in females worldwide. Despite the available prevention and early detection strategies, carcinoma of the uterine cervix is still diagnosed as locally advanced disease in a considerable proportion of patients. Standart treatment of locally advanced cervical cancer is cisplatin-based chemoradiation. Unfortunately, results of the treatment are not sufficient and cancer relapses are frequent. New cytostatics regimens either alone or in combination with cisplatin are searching as radiosensitizers with concurrent radiotherapy. Neoadjuvant/induction chemotherapy, adjuvant/consolidation chemotherapy strategies, molecular agents targeting critical pathways are under investigation in clinical trials to improve results of the treatment. The purpose of this article is overview of currently available knowledge found in literature about the chemoradiation for locally advanced cervical cancer. Key words: locally advanced cervical cancer, chemoradiation, adjuvant/consolidation chemotherapy, neoadjuvant/induction chemotherapy. Chemospindulinis vietiškai išplitusio gimdos kaklelio vėžio gydymas Straipsnio tikslas – apžvelgti ir pateikti šiuo metu prieinamoje literatūroje sukauptas žinias apie konservatyvų chemospindulinį vietiškai išplitusio gimdos kaklelio vėžio gydymą. Gimdos kaklelio vėžys yra trečia dažniausiai pasaulyje nustatoma moterų vėžio forma ir ketvirta pagal dažnį moterų mirties nuo vėžio priežastis. Nepaisant profilaktikos priemonių bei patikros programos, nemaža dalis gimdos kaklelio vėžio atvejų nustatoma jau vietiškai išplitusios IIB–IVA stadijos. Šiuo metu vietiškai išplitusio gimdos kaklelio vėžio gydymo standartas – suderintas chemospindulinis gydymas cisplatinos pagrindu. Deja, gydymo rezultatai nėra patenkinami, atkryčio dažnis išlieka didelis. Siekiant geresnių gydymo rezultatų atlikta ir atliekama daug klinikinių tyrimų, spindulinio gydymo metu taikant naujus citostatikus ar jų derinius su cisplatina, tiriama neoadjuvantinės/indukcinės bei adjuvantinės/konsoliduojančios chemoterapijos reikšmė, „taikinių“ terapijos panaudojimo galimybė. Reikšminiai žodžiai: vietiškai išplitęs gimdos kaklelio vėžys, chemospindulinis gydymas, adjuvantinė/konsoliduojanti chemoterapija, neoadjuvantinė/indukcinė chemoterapija.